Measuring Attitudes Toward Nursing Safety Violations. Issue 1 (February 2016) - Adachi, Yuko; Usui, Shinnosuke; Nakagami-Yamaguchi, Etsuko; Fujinaga, Kumiko; Park, Keunsik; Nakamura, Kazunori; Nakatani, Tatsuya
This study measured implicit and explicit attitudes toward major nursing safety violations using the Implicit Association Test (IAT) and self-reported questionnaires, respectively. Experiment 1 sampled nursing students ( n  = 71), and Experiment 2 sampled patient safety nurses ( n  = 38). Although reaction time to IAT stimuli of major nursing safety violations was quicker than of general nursing behaviors, error trials did not reveal a significant difference between IAT stimuli of major nursing safety violations and of general nursing behaviors in Experiment 1. Explicit attitude was related with intention to violate safety protocols in Experiment 1. In Experiment 2, both reaction time and error trials showed significant differences between IAT stimuli of major nursing safety violations and of general nursing behaviors. This was interpreted in that patient safety nurses had formed a firm implicit attitude, unlike the nursing students; however, the findings suggested that attitudes were not related to violations in nursing.